2015
DOI: 10.4025/actascibiolsci.v37i1.22731
|View full text |Cite
|
Sign up to set email alerts
|

<b>Optimization of culture conditions for tannase production by <i>Aspergillus</i> sp. gm4 in solid state fermentation

Abstract: ABSTRACT.Tannase is an industrially important enzyme produced by a large number of microorganisms. This study analyzed the production of tannase by Aspergillus sp. GM4 under solid-state fermentation (SSF) using different vegetable leaves (mango, jamun and coffee) and agricultural residues (coffee husks, rice husks and wheat bran). Among the substrates used jamun leaves yielded high tannase production. The Plackett-Burman design was conducted to evaluate the effects of 12 independent variables on the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…According to Souza et al . (), Aspergillus fungi are widely studied for tannase production. Yao et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Souza et al . (), Aspergillus fungi are widely studied for tannase production. Yao et al .…”
Section: Resultsmentioning
confidence: 99%
“…Using agar medium containing tannic acid to select tannase producer fungi, Bhoite & Murthy (2014) reported that a relation between degradation halo size and colony diameter can be used as an efficient indicator of the micro-organism's secretion of tannase. According to Souza et al (2015), Aspergillus fungi are widely studied for tannase production. Yao et al (2014b) indicated that other fungi besides Aspergillus, such as Penicillium, Fusarium and Trichoderma, can also be used for tannase production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain Aspergillus sp. GM4 presented enzymatic activity values of 0.13 ± 0.04 to 1.44 ± 0.43 U (mg of protein) -1 , (Souza et al, 2015). Shi et al (2005), found tannase activity in the strain C. uilis with values of 32 U cm -3 with 9 days of fermentation.…”
Section: Enzymatic Activitymentioning
confidence: 88%
“…Enzim selulase nantinya akan merombak serat kasar daun teh terbuang menjadi monomer yang lebih sederhana, sehingga mudah untuk dicerna oleh ternak. Selain mampu menghasilkan beberapa enzim seperti xylanase, phytase (Nair dan Duvnjak, 1990) dan tanase (Souza et al, 2015). Tanase merupakan enzim yang digunakan untuk mengkatalis reaksi pemutusan ikatan ester tanin terhidrolisis membentuk asam galat dan glukosa.…”
Section: Pendahuluanunclassified